IMPROVING ORGANIZATIONAL CITIZENSHIP BEHAVIOUR THROUGH TRANSFORMATIONAL LEADERSHIP STYLE AND ORGANISATIONAL CLIMATE THROUGH JOB SATISFACTION - Moch. Ichsan Nugraha; Sri Harini; Erni Yuningsih (Jurnal Visionida, 2024)
This research aims to analyze the influence of transformational leadership, organizational climate, organizational citizenship behavior (OCB), through job satisfaction as an intervening variable in PT. Japfa Comfeed Indo Tbk Unit Hatchery Parungkuda. This type of quantitative research uses descriptive research design and verification using path analysis and Sobel test methods. The data collection process uses field research and library research. The number of samples used in this research was 92 employees using random sampling techniques. The results of this research show that transformational leadership has a direct positive and significant effect on job satisfaction, organizational climate has a direct positive and significant effect on job satisfaction, job satisfaction has a direct positive and significant effect on OCB, transformational leadership has a direct positive and significant effect on OCB through job satisfaction as a variable intervening, organizational climate has a direct positive and significant effect on OCB through job satisfaction as an intervening variable Keywords: Organizational Citizenship Behavior, Transformational Leadership, Organizational Climate, Job Satisfaction.